A gestão de recursos humanos nas Organizações Não Governamentais de cooperação para o desenvolvimento portuguesas : uma análise interpretativa exploratória - Vanessa Marcos (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
In the light of the theoretical-empirical debate on the instrumentalization of volunteering and on the precarization of the labor market, in this article we problematize human resources management in NonGovernmental Development Organizations (NGDOs) regarding their higher and lower orientation to professionalization as an organizational strategy of efficiency and efficacy. Through data collected from a survey applied to 23 Portuguese NGDOs intentionally selected we present a general characterization of their paid workers and volunteers as well as an interpretative analysis of the human resources’ management practices.